Curricular training report: clinical studies coordination in a clinical research organization vs an investigational site perspective - Oliveira, Joana Pereira (2016)
This report describes my experience of nine months as a trainee of a CRO (Eurotrials, Scientific Consultants), as well as a trainee of a clinical research site (Clinical Academic Center – Braga, Association). This document describes the European framework about clinical research and the Portuguese situation compared to similar countries. The activities developed during this internship are also described. These activities are divided in two phases. The first one occurred in Eurotrials, Scientific Consultants, a CRO specialized in clinical research and scientific advice. The first weeks were dedicated to intensive self-training needed to perform CTA tasks. These tasks included qualification, initiation and monitoring activities related to clinical trials, as well as the development of a quality management system. The second phase took place on 2CA-Braga, a clinical research center located in Hospital of Braga. Clinical studies coordination was the main focus of this second phase of my internship, as well as negotiation of clinical studies agreements. I had also the opportunity to participate in “1as Jornadas de Investigação Clínica e Inovação” (1st Clinical Investigation and Innovation Conference) organized by 2CA-Braga. Globally, this internship was a great opportunity to get knowledge and experience in the implementation and management of clinical trials, in a CRO and clinical research site perspectives. These two perspectives provided an interesting overview about the scientific needs of different players involved in clinical research. To conclude, this internship strengthened the knowledge acquired from my academic background, which make me able to face and overcome new challenges in the clinical research area.